Efektifitas Metode Sitz Bath Dengan Rebusan Daun Belimbing Wuluh Terhadap Penurunan Nyeri Luka Perineum Pada Ibu Post Partum - Irma Jayatmi; Ineu Nurjanah; Ernita Prima (SIMFISIS Jurnal Kebidanan Indonesia, 2022)
Introduction: According to the World Health Organization (WHO), nearly 90% of normal birth process suffered a tear in the perineum either with or without episiotomy. In 2009, 2.7 million cases occurred tear (rupture) in the maternal perineum. This figure is estimated at 6.3 million. Objectives: The purpose of this study was to determine the effectiveness of the sitz bath method with starfruit leaf decoction compared to the sitz method with cold water to reduce pain in perineal wounds in post partum mothers Method: This study uses an quasi experimental research method with a pre and post control group design, the number of samples of 20 respondents obtained by accidental sampling technique. Data were processed using SPSS Version 23. Result: Mann Whitney U Test Results Based on the results of research data processing, the value of Asymp. Sig. (2-tailed) of 0.000 <0.05, it can be concluded that there is an effect of using the Sitz Bath method of Belimbing Wuluh Leaves on reducing post partum maternal wound pain. Conclusion: Conclusion there is influence of sitz bath with a decoction method starfruit leaves compared with sitz method with cold water to decrease maternal perineal wound pain post partum. Keyword: for post partum mothers can be used as a reference for midwifery interventions to reduce perineal pain in post partum mothers by using the sizt bath method of starfruit leaf boiled water to reduce perineal wound pain.